Adaptación y rendimiento de siete líneas de arroz (oryza sativa), bajo el sistema de siembra al voleo en el Huallaga Central San Martín - Díaz Chávez, Rusbelt Rogelio (2004)
The present work has as title “Adaptation and yiek1 of seven lines of rice (oryza saliva), under the siembra system to the I volley in the central Huallaga San Martín”, likewise with the objective you to determine the best variety in the experiment, with direct siembra under the environmental conditions of the Central Huallaga and to carry out the economic analysis of the treatments; he / s he was carried out the present world in the lands that it drives the Company Mils May CORP, located in the District or rich Port, County of Pillory Department of San Martin.; with an annual maximum Tº of 32 °C , precipitation averages yearly of 1000 - 1 200 mm and a relative humidity of 70-80%. The used design was at random or Complete Blocks (DBCA), with 9 treatment with three repetitions. The treatments were T1 (EPAGRl-107), T2 (EPAGRl-108), T3 (EPAGRl-109), T4 QAC-101), T5 (QAC-103), T6 (QAC-202), T7 (IAC-238), T8 (Q NIA501), T9 (CAPIRONA). The results demonstrated that the biggest yields in she´s for hectare were obtained in the Treatments 9 (CAPIRONA) with 7636,33 kilos and 8 (QNJA-501) with 6984,57 kilos and the biggest macollamiento ability obtained the treatment 8 (INIA-501) with 218,37 macollas for M2.Mientras that the biggest precocity that or he/she showed to have the treatment 2 (EPAGRl-108) with 121,80 days to the maturity and the plant of smaller height obtained if the treatment 2 (EPAGRl.1108) with 107..00 same cm Asl the biggest quality molinera obtained them the treatment 8 (Q NIA501) with 72,90% and lastly the biggest weight In the 1000 grains obtained it the treatment a -O NIA-501) with 32,13 g.